Competitive tendering in local and regional public transport in the Netherlands - Didier M. van de Velde; Fons Savelberg (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This paper reviews evidence on the performance of urban public transport governance regimes in place in the Netherlands over the past 15 years. The national government decided to move from a system of ad hoc subsidy payments to one with more decentralised government control and tendering, though approaches varied across Jurisdictions. In each jurisdiction, the government agency determines the services required; in major urban areas, services are delivered by the public operators, while elsewhere services are delivered by private operators selected through competitive tendering. The available evidence suggests that the reformed system has delivered good customer satisfaction and cost effectiveness - even in jurisdictions without tendering - though no positive influence of the reform on ridership could be established.
Keywords: 330; Öffentlicher Nahverkehr; Regionalverkehr; Ausschreibung; Auktionstheorie; Niederlande